1998
DOI: 10.2108/zsj.15.799
|View full text |Cite
|
Sign up to set email alerts
|

A New Population of the Amphioxus (Branchiostoma belcheri) in the Enshu-Nada Sea in Japan

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 7 publications
(12 reference statements)
2
18
0
Order By: Relevance
“…This reinforces the suggestion that spawning may have occurred in late MayeJune and that the recruitment period would follow through JuneeOctober, where it achieves maximum abundances. Similar behavior has been observed with the Florida amphioxus, Branchiostoma floridae, with a breeding season from early May to early September and new lancelet juveniles from late May through mid-October (Stokes, 1996; Table 1), and with the east-Asian amphioxus, Branchiostoma belcheri, which also showed a breeding season from June to August concentrating large number of juveniles in September (Kubokawa et al, 1998;Yamaguichi and Henmi, 2003; Table 1). It was not possible to determine the life span of B. lanceolatum.…”
Section: Branchiostoma Lanceolatumsupporting
confidence: 70%
“…This reinforces the suggestion that spawning may have occurred in late MayeJune and that the recruitment period would follow through JuneeOctober, where it achieves maximum abundances. Similar behavior has been observed with the Florida amphioxus, Branchiostoma floridae, with a breeding season from early May to early September and new lancelet juveniles from late May through mid-October (Stokes, 1996; Table 1), and with the east-Asian amphioxus, Branchiostoma belcheri, which also showed a breeding season from June to August concentrating large number of juveniles in September (Kubokawa et al, 1998;Yamaguichi and Henmi, 2003; Table 1). It was not possible to determine the life span of B. lanceolatum.…”
Section: Branchiostoma Lanceolatumsupporting
confidence: 70%
“…Adult amphioxus, Branchiostoma belcheri , were collected from the Enshu‐nada Sea, Japan (Kubokawa et al, '98) and from Tsuyazaki, near the Fishery Research Laboratory of Kyushu University, Japan. Note that Zhang et al (2006a,b) showed evidences that B. belcheri actually consists of two distinct species, and according to their classification our specimens are B. japonicum .…”
Section: Methodsmentioning
confidence: 99%
“…Belonging to the subphylum Cephalochordata, lancelets share key anatomical and developmental features with vertebrates and tunicates and have proved crucial in understanding the morphology and evolution of chordates in general. In contrast, the main aspects of the population ecology of most species are poorly known (Chen et al, 2008) in spite that: (i) they may play an important role in marine food webs by transferring substantial amounts of microbial production to higher trophic levels (Chen, 2007); and (ii) the conservation status of some populations have already been considered under the category of endangered species (Kubokawa et al, 1998). Putnam et al, 2008).…”
Section: Introductionmentioning
confidence: 99%